Wechsler Administration and Scoring Errors Made by Graduate Students and School Psychologists. (September 2019) - Oak, Erika; Viezel, Kathleen D.; Dumont, Ron; Willis, John
Individuals trained in the use of cognitive tests should be able to complete an assessment without making administrative, scoring, or recording errors. However, an examination of 295 Wechsler protocols completed by graduate students and practicing school psychologists revealed that errors are the norm, not the exception. The most common errors included failure to administer sample items, incorrect calculation of raw scores, failure to record responses verbatim, and failure to query. Significant differences were found between specific error frequencies of students and practitioners. Adequate training in administering the Wechsler scales is clearly essential. Based on the outcome of this study, it is recommended that programs training students to administer cognitive assessments provide ample feedback, and that practicing psychologists maintain best practices and take part in continuing education regarding cognitive assessments.